2018
DOI: 10.1186/s12913-018-3637-1
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary first-day consultation accelerates diagnostic procedures and throughput times of patients in a head-and-neck cancer care pathway, a mixed method study

Abstract: BackgroundHead and neck cancers are fast growing tumours that are complex to diagnose and treat. Multidisciplinary input into organization and logistics is critical to start treatment without delay. A multidisciplinary first-day consultation (MFDC) was introduced to reduce throughput times for patients suffering from head and neck cancer in the care pathway. In this mixed method study we evaluated the effects of introducing the MFDC on throughput times, number of patient hospital visits and compliance to the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Multidisciplinary first-day consultation intents to shorten time between diagnosis and treatment of oral cancer (van Huizen et al, 2018).…”
Section: Pre Tre Atment Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidisciplinary first-day consultation intents to shorten time between diagnosis and treatment of oral cancer (van Huizen et al, 2018).…”
Section: Pre Tre Atment Screeningmentioning
confidence: 99%
“…Multidisciplinary first‐day consultation intents to shorten time between diagnosis and treatment of oral cancer (van Huizen et al., 2018). Maxillofacial prosthodontics should be included in the multidisciplinary first‐day consultation.…”
Section: Pretreatment Screeningmentioning
confidence: 99%
“…The efficiency of the MDTs is important for decision-making and care pathway management. The centre’s MDT regarding diagnostics and treatment involves more than nine disciplines (details presented elsewhere) 13. The teams of centre and partner meet face-to-face three times a year, where governance, guidelines and research projects are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Toustrup et al revealed that a fast track strategy with a full-time case manager, multidisciplinary tumor board, and higher priority for head and neck cancer examination slots could dramatically shorten the time between the initial visit and the start of curative treatment, from 57 to 29 days [25]. Van Huizen et al found that multidisciplinary rst-day consultation might shorten the days needed for diagnostic procedures and the days to the start of the rst treatment in patients with head and neck cancer [26]. They concluded that the introduction of a multidisciplinary rst-day consultation, including specialists of different departments and the use of coordinating nurses, could improve treatment quality.…”
Section: Discussionmentioning
confidence: 99%